Observations on the Growth of Young Tinfoil Barb, Puntius schwanenfeldii (Bleeker) Fed with Pellet Feeds - Mohammad Mohsin, Abu Khair; Jee, Ang Kok (1979)
A study was conducted to test the suitability of four feeds formulated from agricultural by-products for tinfoil barb fry. The crude protein levels in feeds 1, 2, 3 and 4 'were 14.5, 18.6,.16.9 and 13.1 per cent respectively. F1Sh fed diet 2 attained maximum growth compared to fishes fed other diets (P < O.O5).